The impact of idealism, Volume 4, Religion the legacy of post-Kantian German thought - Adams, Nicholas 1970-; Boyle, Nicholas; Disley, Liz (Cambridge University Press, 2013)
The first study of its kind, The Impact of Idealism assesses the impact of classical German philosophy on science, religion and culture. This fourth volume explores German Idealism's impact on theology and religious ideas in the nineteenth, twentieth and twenty-first centuries. With contributions from leading scholars, this collection not only demonstrates the vast range of Idealism's theological influence across different centuries, countries, continents, traditions and religions, but also, in doing so, provides fresh insight into the original ideas and themes with which Kant, Hegel, Fichte, Schelling and others were concerned. As well as tracing out the Idealist influence in the work of nineteenth- and twentieth-century theologians, philosophers of religion, and theological traditions, from Schleiermacher, to Karl Barth, to Radical Orthodoxy, the essays in this collection bring each debate up to date with a strong focus on Idealism's contemporary relevance